Prevalence of Prediabetes is Increasing Among U.S. Youth. Issue 5 (September 2022) - Beal, Judy A.
Abstract : The prevalence of prediabetes, diabetes, overweight, and obesity is increasing among U.S. youth. Our pediatric nursing expert, Dr. Beal, discusses highlights of recent research and makes recommendations for clinical practice for pediatric nurses.